2007
DOI: 10.1016/j.acn.2007.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Performance on a neurocognitive measure of alerting differentiates ADHD combined and inattentive subtypes: A preliminary report

Abstract: The performance of 16 attention-deficit hyperactivity disorder (ADHD)/C, 26 ADHD/IA, and 24 control children was compared using a computer reaction time task designed to measure the effects of Posner's orienting, conflict and alerting attentional systems. No group differences in orienting or conflict were found. In contrast, children with ADHD/IA showed stronger alerting effects than those with ADHD/C, as indicated by relatively greater performance benefits following a warning cue. Although neither ADHD group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
79
4
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(94 citation statements)
references
References 24 publications
10
79
4
1
Order By: Relevance
“…However, some other researchers suggested that the alerting network can best detect inattentive ADHD (Booth et al, 2007). For example, Booth et al (2007) found that children with inattentive type ADHD showed a stronger alerting effect than those with the combined type ADHD, but no group differences were found in orienting and executive attention. A neuroimaging study also suggested that children with ADHD had a deficit in alerting, and this deficit was related to abnormal activities in the frontal and parietal brain regions (Cao et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some other researchers suggested that the alerting network can best detect inattentive ADHD (Booth et al, 2007). For example, Booth et al (2007) found that children with inattentive type ADHD showed a stronger alerting effect than those with the combined type ADHD, but no group differences were found in orienting and executive attention. A neuroimaging study also suggested that children with ADHD had a deficit in alerting, and this deficit was related to abnormal activities in the frontal and parietal brain regions (Cao et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Using the ANT, several researchers reported alerting and executive attention deficits in children with ADHD (Johnson et al, 2008;Mullane et al, 2011). However, some other researchers suggested that the alerting network can best detect inattentive ADHD (Booth et al, 2007). For example, Booth et al (2007) found that children with inattentive type ADHD showed a stronger alerting effect than those with the combined type ADHD, but no group differences were found in orienting and executive attention.…”
Section: Discussionmentioning
confidence: 99%
“…Up till now, few studies have investigated potential differences in the efficiency of attentional networks between DSM-IV subtypes of ADHD and results of those studies are inconsistent in that some studies show no differences between subtypes (e.g., Mullane et al, 2011) whereas others suggest that there may be a stronger alerting effect in ADHD of the predominantly inattentive type (ADHD IA) as compared to ADHD combined (e.g., Booth et al, 2007). Given these inconsistent findings, it would be interesting to analyze potential subgroup differences in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Findings on alerting and executive attention are less consistent. Some studies showed differences in the efficiency of executive attention (i.e., a larger interference effect in the ADHD group; e.g., Konrad et al, 2006;Mullane, Corkum, Klein, McLaughlin, & Lawrence, 2011), and/or in the efficiency of alerting (e.g., Casagrande et al, 2012;Johnson et al, 2008;Mullane et al, 2011) whereas others showed no differences in comparison to TD peers (e.g., Ad贸lfsd贸ttir et al, 2008;Booth et al, 2007).…”
mentioning
confidence: 99%
“…Quite contrary to its initial comprehension as a unitary capacity, during recent decades the concept of attention has rather diversified into fragments supported by separable anatomical networks subserving specific differential aspects of attention. Within a clinical context, the three attentional networks model provided by Posner (Petersen & Posner, 2012;Posner, 1980), or variations thereof, have been proven valuable for patient studies not only of neglect (Corbetta, Kincade, Lewis, Snyder, & Sapir, 2005) but also of, for example, attention deficit hyperactivity disorder (Ad贸 lfsd贸 ttir, Srensen, & Lundervold, 2008;Booth, Carlson, & Tucker, 2007;Konrad et al, 2006;Tsal, Shalev, & Mevorach, 2005) or schizophrenia (Wang et al, 2005). With the application of tDCS for deficits of attention in mind, the three attentional networks model may provide a helpful theoretical framework to systematically evaluate the effects of neuromodulation.…”
Section: Theory Of Attentionmentioning
confidence: 99%